2018
DOI: 10.7717/peerj.4361
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of silver nanoparticles using Caesalpinia ferrea (Tul.) Martius extract: physicochemical characterization, antifungal activity and cytotoxicity

Abstract: BackgroundGreen synthesis is an ecological technique for the production of well characterized metallic nanoparticles using plants. This study investigated the synthesis of silver nanoparticles (AgNPs) using a Caesalpinia ferrea seed extract as a reducing agent.MethodsThe formation of AgNPs was identified by instrumental analysis, including ultraviolet–visible (UV–Vis) spectroscopy, scanning electron microscopy (SEM), X-ray diffraction (XRD) of the AgNPs, and surface-enhanced Raman scattering (SERS) spectra of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 53 publications
3
16
0
Order By: Relevance
“…The significant enhancement of the signal at 1000 cm −1 (due to ring breathing and asymmetric stretching vibration of CH 2 in the skeletal chain of PI, TCA, and biomolecules from plant extract) reveals that the CH 2 chain is close to the surface of AgNPs. The results of our SERS analysis are in agreement with previous reports and discussions above [102][103][104][105][106]. The nanocolloidal sample Cinn-AgNP-PI is SERS-inactive ( Figure 9d).…”
Section: Discussionsupporting
confidence: 92%
“…The significant enhancement of the signal at 1000 cm −1 (due to ring breathing and asymmetric stretching vibration of CH 2 in the skeletal chain of PI, TCA, and biomolecules from plant extract) reveals that the CH 2 chain is close to the surface of AgNPs. The results of our SERS analysis are in agreement with previous reports and discussions above [102][103][104][105][106]. The nanocolloidal sample Cinn-AgNP-PI is SERS-inactive ( Figure 9d).…”
Section: Discussionsupporting
confidence: 92%
“…The zone of inhibition values obtained here is similar to those reported by Yasir et al 10 The MICs values of ScAgNPs against all tested Candida and bacteria species ranged from 0.125-0.250 mg/mL, whereas the MBCs and MFCs were 0.250 and 0.500 mg/mL, respectively. In a recent study, 17 AgNPs synthesized by Caesalpinia ferrea seed extract showed MIC values in the range of 156.25-1,250 µg/mL, and MFC values in the range of 312.5-5,000 µg/mL against C. albicans, C. glabrata, C. kruzei, and C. guilliermondii. 17 The MIC and MFC results of the present study demonstrate that the ScAgNPs exhibited high anticandidal activity.…”
Section: Antimicrobial Activity Of Scagnpsmentioning
confidence: 98%
“…The antimicrobial activity of biogenic AgNPs was well documented in the literature. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] However, there are very few studies available in the literature on the inhibition of production of various extracellular hydrolytic enzymes and germ tubes in Candida spp by nanoparticles. [22][23][24] Due to the scarcity in the literature on the inhibition of production of various virulence factors by Candida spp, herein for the first time we have reported the potent inhibitory effects of green synthesized AgNPs on the production of different virulence attributes of Candida species isolated from oropharyngeal mucosa of HIV patients.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, due to the rich Brazilian biodiversity, some studies in the literature related the use of endemic plants of the country for producing AgNPs [7][8][9]. However, there are no published reports mentioning the use of Pterodon emarginatus (white sucupira) leaf extracts for this purpose.…”
Section: Introductionmentioning
confidence: 99%